2017
DOI: 10.1038/s41598-017-18086-3
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise improves endothelial function and serum adropin levels in obese adolescents independent of body weight loss

Abstract: Adropin is a secreted protein that regulates endothelial function. However, adropin levels in obese adolescent patients are currently uncertain. Therefore, we evaluated the association between plasma adropin levels and vascular endothelial function and investigated the effect of aerobic exercise in obese adolescents. A total of 45 obese adolescents and 20 controls (age 16–19 years) were included in our study. The obese adolescents received 12 weeks of aerobic exercise training. Serum adropin was detected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 34 publications
6
43
1
Order By: Relevance
“…Thus, it is possible that adropin may promote arterial stiffness via NO-dependent signaling [53]. In line with this data, physical exercise upregulates circulating adropin in humans, which is accompanied by improved endothelial function [54]. Overall, these results suggest that low levels of adropin are associated with cardiovascular complication, such as endothelial dysfunction, cardiac syndrome X, or hypertension.…”
Section: Adropin In the Cardiovascular Systemsupporting
confidence: 69%
“…Thus, it is possible that adropin may promote arterial stiffness via NO-dependent signaling [53]. In line with this data, physical exercise upregulates circulating adropin in humans, which is accompanied by improved endothelial function [54]. Overall, these results suggest that low levels of adropin are associated with cardiovascular complication, such as endothelial dysfunction, cardiac syndrome X, or hypertension.…”
Section: Adropin In the Cardiovascular Systemsupporting
confidence: 69%
“…Zhang et al (50) found IR index is a negative independent risk factor of ADR levels in obese adolescents. Yosaee et al (51) reported that subjects with metabolic syndrome had significantly lower ADR levels and adropin/leptin ratio and ADR levels were correlated with metabolic syndrome and hence is a potentially protective agent against its development.…”
Section: Discussion:-mentioning
confidence: 99%
“…Kumar et al suggested that adropin is an hepatokine that is decreased in diet-induced obese mice and showed that transgenic overexpression or systemic adropin treatment attenuated steatosis by suppressing the expression of Fas and the gene for Stearoyl-CoA desaturase-1 ( Scd1 ) ( 80 ). Aerobic training increased serum adropin levels in humans, and this was associated with reduced arterial stiffness ( 84 ) and improvements in endothelial function ( 85 ).…”
Section: Mechanisms By Which Exercise Improves Nafld; a Narrative Revmentioning
confidence: 99%